Lesbians in Revolt - Bunch, Charlotte (Lesbianism and the women's movement, 1975)
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; lesbianisme; militance; mouvements des femmes*; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; thématiques; états-unis

Lesbianism and the women's movement - Myron, Nancy; Bunch, Charlotte (Diana Press, 1975)
This book outlines the essence of lesbian/feminist politics and documents how the women's movement has responded to it. In so doing it critiques heterosexuality and shows why lesbianism is one of the fundamental issues of feminism today. The articles collected here were written by the Furies and/or taken from Furies publications over a two-year period.
Keywords: 1900-1999; approches et analyses; cours; fem1000; lesbianisme; militance; mouvements des femmes*; premier cycle; périodes historiques; thématiques